Studies on Stigma Receptivity and Pollen Viability in Parental Lines of Phule Aadishakti Hybrid of pearlmillet as Affected by Different Seasons - TJ JADHAV; PY SHINDE; MT BHINGARDE; KK BARHATE; DS THAKARE (Seed Research, 2025)
Stigma receptivity and pollen viability are critical determinants of successful hybrid seed production in pearl millet (Pennisetum glaucum (L.) R. Br.), particularly in male-sterility–based hybrid breeding systems. The present investigation was undertaken to study the effect of seasons on stigma receptivity and pollen viability in parental lines of the Phule Aadishakti pearl millet hybrid during Kharif and summer seasons. The experimental material comprised the male-sterile line DHLB-8A (female parent), the maintainer line DHLB-8B, and the restorer line DHLB-967 (male parent). Stigma receptivity was evaluated under six starvation interval treatments (0, 1, 2, 3, 4, and 5 days), while pollen viability was assessed at six pollination intervals (0, 2, 4, 6, 8, and 10 hours). Seed set percentage, number of seeds per earhead, seed weight per earhead, and 1000-seed weight were recorded to assess reproductive success. Results revealed that both stigma receptivity and pollen viability were significantly influenced by season, with superior performance observed during the Kharif season compared to the summer season. Higher seed set and yield attributes in Kharif indicated more favorable environmental conditions for reproductive processes. The findings highlight the importance of optimizing season-specific flowering synchronization and pollination timing for efficient hybrid seed production. This study provides valuable insights for improving seed yield and quality in pearl millet hybrid breeding and commercial seed production programs.